Time driven activity based costing - metoda aktualizująca rachunek kosztów działań - Dłubak, Marcin (Time driven activity based costing - the updated method of activity based costing, 2006)
The article a new approach to Activity Based Costing which is called Time Driven Activity presents Based Costing and was created by Kaplan and Anderson. Difficulties arisen in traditional Activity Based Costing led to updated version of this cost accounting system called Time Driven Activity Based Costing. The article shows the simplicity of cost calculation under Time Driven Activity Based Costing and possibilities of modernizing and using this method in practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 80-86